You Have One New Message: Knitting intimacy for connecting opinions, people and the world - Aktas, Bilge Merve (FormAkademisk, 2021)
Knitting is often practiced as a group activity that takes place in the domestic environment. Besides the collectivity, using motifs with meanings has also facilitated communication between people. Building on these ideas, a workshop was designed to facilitate discussions about everyday concerns or experiences, both on personal and societal levels, to strengthen communication with the self and others. In the workshop, the thirteen participants were asked to design a motif to convey a message to themselves, to the group or to the society. Through a group discussion, the motifs stemming from personal experiences were knitted, shared and discussed. The topics emerging from the workshop indicates that knitting affords intimate exchanges between the self and others, and connects people by facilitating socio-political discussions, such as on environmental sustainability, women rights and self-development.